Biological effects of tritium on fish cells in the concentration range of international drinking water standards. (2nd October 2016) - Stuart, Marilyne; Festarini, Amy; Schleicher, Krista; Tan, Elizabeth; Kim, Sang Bog; Wen, Kendall; Gawlik, Jilian; Ulsh, Brant
Abstract: Purpose: To evaluate whether the current Canadian tritium drinking water limit is protective of aquatic biota, an in vitro study was designed to assess the biological effects of low concentrations of tritium, similar to what would typically be found near a Canadian nuclear power station, and higher concentrations spanning the range of international tritium drinking water standards. Materials and methods: Channel catfish peripheral blood B-lymphoblast and fathead minnow testis cells were exposed to 10–100, 000 Bq l −1 of tritium, after which eight molecular and cellular endpoints were assessed. Results: Increased numbers of DNA strand breaks were observed and ATP levels were increased. There were no increases in γH2AX-mediated DNA repair. No differences in cell growth were noted. Exposure to the lowest concentrations of tritium were associated with a modest increase in the viability of fathead minnow testicular cells. Using the micronucleus assay, an adaptive response was observed in catfish B-lymphoblasts. Conclusions: Using molecular endpoints, biological responses to tritium in the range of Canadian and international drinking water standards were observed. At the cellular level, no detrimental effects were noted on growth or cycling, and protective effects were observed as an increase in cell viability and an induced resistance to a large challenge dose.